Stress and Corticosteroids Aggravate Morphological Changes in the Dentate Gyrus after Early-Life Experimental Febrile Seizures in Mice - van Campen, Jolien S.; Hessel, Ellen V. S.; Bohmbach, Kirsten; Rizzi, Giorgio; Lucassen, Paul J.; Lakshmi Turimella, Sada; Umeoka, Eduardo H. L.; Meerhoff, Gideon F.; Braun, Kees P. J.; de Graan, Pierre N. E.; Joëls, Marian (Frontiers in Endocrinology, 2018)
Stress is the most frequently self-reported seizure precipitant in patients with epilepsy. Moreover, a relation between early-life stress and epilepsy has been suggested. Although early-life stress and stress hormones are known to influence seizure threshold in rodents, effects on the development of epilepsy (epileptogenesis) are still unclear. Therefore, we studied the consequences of early-life corticosteroid exposure for epileptogenesis, under highly controlled conditions in an animal model. Experimental febrile seizures were elicited in 10-days-old mice by warm-air induced hyperthermia, while a control group was exposed to a normothermic condition. In the following 2 weeks, mice received either seven corticosterone or vehicle injections or were left undisturbed. Specific measures indicative for epileptogenesis were examined at 25-days of age and compared with vehicle injected or untreated mice. We examined structural (neurogenesis, dendritic morphology and mossy fiber sprouting) and functional (glutamatergic postsynaptic currents and long-term potentiation) plasticity in the dentate gyrus. We found that differences in dentate gyrus morphology induced by experimental febrile seizures were aggravated by repetitive (mildly stressful) vehicle injections and corticosterone exposure. In the injected groups, experimental febrile seizures were associated with decreases in neurogenesis, and increases in cell proliferation, dendritic length and spine density. No group differences were found in mossy fiber sprouting. Despite these changes in dentate gyrus morphology, no effects of experimental febrile seizures were found on functional plasticity. We conclude that corticosterone exposure during early epileptogenesis elicited by experimental febrile seizures aggravates morphological, but not functional, changes in the dentate gyrus, which partly supports the hypothesis that early-life stress stimulates epileptogenesis.